Extract Alleviates Inflammation in Kidney and Liver of the 2-Kidney-1-Clip Hypertensive rat - Nattaya Thongsepee PhD; Wanwisa Himakhun MD; Ratsikan Parachat BSc; Pongsakorn Martviset PhD; Pathanin Chantree PhD; Phornphan Sornchuer PhD; Kant Sangpairoj PhD; Siriphun Hiranyachattada PhD (SAGE Publishing, 2024)
Garcinia dulcis (GD) extract possesses anti-hypertensive property that are poorly characterized. This study aimed to investigate an anti-inflammatory effect of GD flower extract in the 2-kidney-1-clip (2K1C) hypertensive compared to sham operative (SO) rat. Male Wistar rats were divided into 2 groups; the 2K1C group in which a silver clip was placed around renal artery to induce hypertension, and the SO normotensive group. Four weeks later, each group of rats were further divided into 2 subgroups, each subgroup was orally gavaged of either corn oil (vehicle) or 50 mg/kg BW GD extract daily for 4 weeks. The malondialdehyde (MDA) levels in serum, liver, and kidney were determined. Hematoxylin and eosin staining was carried out for histological examination, Periodic acid - Schiff staining for glomerular injury, Masson's trichrome staining for renal fibrosis, and immunohistochemistry for either tumor necrosis factor alpha (TNF-α) or endothelial nitric oxide synthase (eNOS) investigation. Taken together, our results demonstrated that GD flower extract decreased the MDA level in both serum and liver and kidney tissue and suppressed the expression of TNF-α in both liver and kidney of 2K1C hypertensive rats. Mesangial cell proliferation, expansion of mesangial matrix, widening Bowman's capsule space, congestion of glomerular capillary and vessel, cloudy swelling of renal tubular epithelial cell, and renal fibrosis were observed in the kidneys of 2K1C rats. Therefore, we concluded that GD flower extract can alleviate liver and kidney inflammation in which partially attenuates the glomerular injury in the 2K1C rat.